The Role, Scope, Health Benefits and Market Growth of Nutraceuticals: An Overview - Ram Narayan Prajapati; Sanjeev Kumar (Current Research in Pharmaceutical Sciences, 2022)
Nutraceuticals are products used as medicines in addition to nutrition. Nutraceuticals can be defined as substances that have physiological benefits or provide protection against chronic disease. Nutraceuticals can be used to improve health, slow down the aging process, prevent chronic diseases, increase life expectancy or support body structure or function. Nutraceuticals are getting a lot of attention these days because of their potential nutritional, safety and therapeutic benefits. Recent studies have shown that these compounds have promising results in various complications. In this review, we have made a great effort in proposing new concepts for nutraceuticals based on disease indications. Highlights herbal remedies that are effective for harsh therapeutic conditions associated with oxidative stress, including allergies, Alzheimer’s disease, cardiovascular disease, cancer, diabetes, eye, immunity, inflammation, and Parkinson’s disease and obesity. These nutraceuticals are used in various diseases, their application, and current market demand. Examples of fish oil preparations, prebiotics and probiotics reviewed.